ANALISA DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KENDARAAN MENGGUNAKAN METODE TOPSIS - P., Diah Arifah (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Transportation vehicle is used by humans to carry out their activities and not infrequently regarded as a basic requirement. At this time so many types of cars from different brands and types . Each type of car has different technical specifications, and every car certainly has its advantages and disadvantages. And this, will result in the prospective car buyers find it difficult to choose the right car and according to desired criteria due to a potential buyer faced with a number of criteria, such as the price of the car, interior accessories, exterior accessories, passenger capacity, year of production, etc. This system is designed to help prospective buyers make decisions in the selection of vehicles, especially cars, so the decision was obtained in accordance with the desired criteria. Â Methods used for this decision is the method TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). This research was carried out by finding the value of each of the alternatives preference and ranking process conducted which will determine the optimal alternative, ie cars that fit the criteria of the consumer. The criteria used are (1) Car Price (C1), (2) Interior Accessories (C2), (3) Exterior Accessories (C3), (4) Year of Production (C4) and (5) Passenger Capacity (C5)Keywoard: Transportation, TOPSIS